Improvement in Finite Sample Properties of the Hansen-Jagannathan Distance Test - Yu Ren; Katsumi Shimotsu (Queen's University, Department of Economics, 2007)
Jagannathan and Wang (1996) derive the asymptotic distribution of the Hansen-Jagannathan distance (HJ-distance) proposed by Hansen and Jagannathan (1997), and develop a specification test of asset pricing models based on the HJ-distance. While the HJ-distance has several desirable properties, Ahn and Gadarowski (2004) find that the specification test based on the HJ-distance overrejects correct models too severely in commonly used sample size to provide a valid test. This paper proposes to improve the finite sample properties of the HJ-distance test by applying the shrinkage method (Ledoit and Wolf, 2003) to compute its weighting matrix. The proposed method improves the finite sample performance of the HJ-distance test significantly.
Keywords: C13; C52; G12; 330; Covariance matrix estimation; Factor models; Finite sample properties; Hansen-Jagannathan distance; Shrinkage method; Ökonometrie; CAPM; Regressionsanalyse